2008
DOI: 10.1016/j.neuron.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Independent Synaptic Transmission Supports a Linear Vestibular Behavior

Abstract: Summary The vestibular system is responsible for transforming head motion into precise eye, head, and body movements that rapidly stabilize gaze and posture. How do central excitatory synapses mediate behavioral outputs accurately matched to sensory inputs over a wide dynamic range? Here we demonstrate that vestibular afferent synapses in vitro express frequency-independent transmission that spans their in vivo dynamic range (5 – 150 spikes/s). As a result, the synaptic charge transfer per unit time is linearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 59 publications
8
94
0
Order By: Relevance
“…However, saturation of postsynaptic receptors reduces the extent of changes in synaptic strength, allowing these synapses to provide a more reliable input to Purkinje cells (Wadiche and Jahr 2001;Foster et al 2002;Blitz et al 2004). For synapses in the vestibular nucleus, steady-state synaptic strength is independent of the frequency of sustained activation (Bagnall et al 2008), unlike most synapses, for which depression increases with elevated stimulus frequencies. This lack of plasticity likely reflects the interactions of multiple presynaptic mechanisms, and contributes to the linearity of vestibular reflexes by allowing this synapse to transmit synaptic charge that is linearly related to stimulus frequency.…”
Section: Short-term Presynaptic Plasticitymentioning
confidence: 99%
“…However, saturation of postsynaptic receptors reduces the extent of changes in synaptic strength, allowing these synapses to provide a more reliable input to Purkinje cells (Wadiche and Jahr 2001;Foster et al 2002;Blitz et al 2004). For synapses in the vestibular nucleus, steady-state synaptic strength is independent of the frequency of sustained activation (Bagnall et al 2008), unlike most synapses, for which depression increases with elevated stimulus frequencies. This lack of plasticity likely reflects the interactions of multiple presynaptic mechanisms, and contributes to the linearity of vestibular reflexes by allowing this synapse to transmit synaptic charge that is linearly related to stimulus frequency.…”
Section: Short-term Presynaptic Plasticitymentioning
confidence: 99%
“…This hypothesis was not experimentally verified on the network level, and in addition its enormous variation seems to prevent reliable information processing [13,14]. Here we experimentally demonstrate neuronal ultra-fast plasticity on a time scale of several milliseconds and its applications to advanced computational tasks.…”
Section: Introductionmentioning
confidence: 77%
“…One component of central vestibular neurons suspected of contributing to their nonlinear of behavior includes the expression of different voltage-dependent K ϩ conductances (Ris et al 2001), which make one type of neuron found in rodent slice preparations (type B) display nonlinear current-discharge relationships. However, other data, also in slice preparations, demonstrate remarkably linear input-output relationships for central vestibular neurons to current (du Lac and Lisberger 1995) and synaptic (Bagnall et al 2008) inputs. Potentially, local circuits may reconcile differences between findings in various preparations and may account for discrepancies in findings regarding linearity of responses in individual neurons (Pfanzelt et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Most of these studies concerned the effect of frequency on the sensitivity and phase of responses of individual neurons and demonstrate a relatively flat relationship for frequencies between 0.1 and 2.0 Hz with an increasing phase lead relative to velocity as the frequency of rotation increases. Although studies of central vestibular neurons in vitro have addressed many aspects of response linearity (Bagnall et al 2008;du Lac and Lisberger 1995;Pfanzelt et al 2008), little systematic work has been done in vivo to understand how the magnitude of stimulation influences responses of central vestibular neurons. The linearity of the responses of central neurons over a range of rotational stimuli has not been directly addressed in normal, alert animals, although such responses have been reported in cats with unilateral vestibular lesions (Heskin-Sweezie et al 2007).…”
mentioning
confidence: 99%